2006
DOI: 10.1111/j.1442-2042.2006.01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of living kidney transplantation from HLA‐identical sibling donors under calcineurin inhibitor immunosuppression

Abstract: Background:Recently, it has been revealed that alloantigen-independent causes are important factors for late graft loss in kidney transplantation. We compared the results of living kidney transplantation from HLA-identical siblings with those from HLA-nonidentical siblings to analyse the impact of alloantigen-independent factors on long-term graft survival. Methods: Two hundred and sixty-six recipients who were grafted from their siblings between 1983 and 2002 were subdivided into those transplanted from HLA-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
0
30
1
1
Order By: Relevance
“…Along with the improved control of acute rejections and infections, the recurrence of primary nephropathy has become the most important cause of graft loss principally for patients who have glomerulonephritis (GN) as the primary disease[1,2]. In some series, recurrence of the original disease was reported to be the principal cause of graft loss more than one year after transplantation[2] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the improved control of acute rejections and infections, the recurrence of primary nephropathy has become the most important cause of graft loss principally for patients who have glomerulonephritis (GN) as the primary disease[1,2]. In some series, recurrence of the original disease was reported to be the principal cause of graft loss more than one year after transplantation[2] (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…In some series, recurrence of the original disease was reported to be the principal cause of graft loss more than one year after transplantation[2] (Table 1). Some renal diseases have a higher risk of recurrence and recurrence-related graft loss.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary immune suppressive regimens have extended the mean transplant survival time in Poland to 8–10 years 46…”
Section: Introductionmentioning
confidence: 99%
“…However, it was noted that the risk of recurrence of the primary disease, which might have been treated with immune suppression is high 2 6. Moreover, it was observed that during the intrauterine fetus growth DNA mutation is often observed, resulting in phenotypic and genotypic divergence even in homozygous twins.…”
Section: Introductionmentioning
confidence: 99%
“…Although there were no major complications, episodes of neutropenic fever, pyelonephritis and viral infections were reported (1 CMV, 1 EBV and 3 varicella zoster). Since the long-term graft survival and overall outcomes of HLA-identical living donor kidney transplants are remarkably good [10], the justification for induction of tolerance in these patients is questionable. The Stanford group also attempted to apply this protocol to the HLA mismatched kidney transplant recipients [11,] but rejection occurred in three of four patients when immunosuppression was tapered [12].…”
Section: Chimerism In Human Kidney Transplantationmentioning
confidence: 99%